A Review of Chinese Herbal Medicine for the Treatment of Chronic Heart Failure - Wang, Yong; Wang, Qiyan; Li, Chun; Lu, Linghui; Zhang, Qian; Zhu, Ruixin; Wang, Wei (Current Pharmaceutical Design, 2017)
Heart failure is one of the major causes of mortality worldwide and it is the end stage of several cardiovascular diseases. Traditional Chinese medicine has been used in the management of heart failure for a long time. Only until recently, well-designed clinical trials have been put into practice to study the efficacies of Chinese herbs. Extensive studies have also been carried out to explore the underlying mechanisms of pharmaceutical actions of Chinese herbs. In this study, we will summarize the frequently used Chinese herbs, formulae and patent Chinese drugs in treating patients with heart failure and review published clinical evaluations of Chinese herbs in treating cardiovascular diseases. The mechanisms by which Chinese herbs exert cardio-protective effects will also be reviewed. In the end, we will point out the limitations of current studies and challenges facing modernization of traditional Chinese medicine.
Keywords: Chinese herbs